Antiproliferative effect of Coleus Neochilus extract on human breast cancer cell lines - Mayora Justel, Carla Luciana (2022)
The Plectranthus species have a rich diversity of ethnobotanical uses. Nevertheless, the most frequently use of these species is for their medicinal properties. This work focuses on Coleus neochilus (Schltr.) Codd, also known as “boldo rastrero” (BR), a specie closely akin to the genus Plectranthus, and its effect on human breast can- cer cell lines. A crude ethanolic extract of leaves of BR was prepared. BR incubation decreased cell viability in MCF-7, MDA-MB-231 and T47D cancer cell lines. The extract concentration that caused a 50% inhibition in cell viability (IC50) was lower for tumor cells than for non- tumor cells (about 45, 19, 26 vs 50 for MCF-7, MDA-MB-231, T47D and MCF-10A respectively). At 10 μg/ml, BR reduced cell prolifera- tion in all tumor cells but not in non-tumor cells (i.e., 45% reduction in MCF-7, p<0.001). An additive effect of BR with therapeutic drugs was observed on reduction of cell viability (MCF-7 cells: BR: 14% reduction, 10 μM tamoxifen (Tx): 53% reduction, BR+Tx: 67% re- duction; MDA-MB-231 cells: BR: 25% reduction, 10 nM paclitaxel (Px): 36% reduction, BR+Px: 53% reduction). Using a colorimetric assay, we detected a 24 % increase in caspase activity after 12 h (p<0.05), suggesting a BR-mediated apoptosis induction. Oxidative stress was not induced after BR exposure. From the original etha- nolic extract, three different fractions were obtained by extraction with different solvents: chloroform, ethyl acetate, methanol-water. In MCF-7 and MDA-MB-231 cells, reduced cell viability was observed only after incubation with the chloroform fraction, indicating the pres- ence of bioactive molecules responsible for the cytotoxic effect. In conclusion, these results demonstrate the antiproliferative proper- ties of BR on breast cancer cells. Moreover, a new additive effect of clinical therapeutic drugs and BR in tumoral cells was described.